International management culture, strategy, and behavior - Hodgetts, Richard M.; Luthans, Fred; Doh, Jonathan P. (McGraw-Hill, 2006)
In the sixth edition of International Management, we have taken care to retain the effective foundation gained from research and practice over the past decades. At the same time, we have fully incorporated important new and emerging developments that have changed what international managers are currently facing and likely to face in the coming years. Of special importance is that students of international management understand what will be expected of them from the range of stakeholders with whom they interact.